Poly(peptide): Synthesis, Structure, and Function of Peptide-Polymer Amphiphiles and Protein-like Polymers - Callmann, Cassandra E; Thompson, Matthew P; Gianneschi, Nathan C (Accounts of chemical research, 2020)
In this Account, we describe the organization of functional peptides as densely arrayed side chains on polymer scaffolds which we introduce as a new class of material called poly(peptide). We describe two general classes of poly(peptide): (1) Peptide-Polymer Amphiphiles (PPAs), which consist of block copolymers with a dense grouping of peptides arrayed as the side chains of the hydrophilic block and connected to a hydrophobic block that drives micelle assembly, and (2) Protein-like Polymers (PLPs), wherein peptide-brush polymers are composed from monomers, each containing a peptide side chain. Peptides organized in this manner imbue polymers or polymeric nanoparticles with a range of functional qualities inherent to their specific sequence. Therefore, polymers or nanoparticles otherwise lacking bioactivity or responsiveness to stimuli, once linked to a peptide of choice, can now bind proteins, enter cells and tissues, have controlled and switchable biodistribution patterns, and be enzyme substrates (e.g., for kinases, phosphatases, proteases). Indeed, where peptide substrates are incorporated, kinetically or thermodynamically driven morphological transitions can be enzymatically induced in the polymeric material. Synergistically, the polymer enforces changes in peptide activity and function by virtue of packing and constraining the peptide. The scaffold can protect peptides from proteolysis, change the pharmacokinetic profile of an intravenously injected peptide, increase the cellular uptake of an otherwise cell impermeable therapeutic peptide, or change peptide substrate activity entirely. Moreover, in addition to the sequence-controlled peptides (generated by solid phase synthesis), the polymer can carry its own sequence-dependent information, especially through living polymerization strategies allowing well-defined blocks and terminal labels (e.g., dyes, contrast agents, charged moieties). Hence, the two elements, peptide and polymer, cooperate to yield materials with unique function and properties quite apart from each alone. Herein, we describe the development of synthetic strategies for accessing these classes of biomolecule polymer conjugates. We discuss the utility of poly(peptide)-based materials in a range of biomedical applications, including imaging of diseased tissues (myocardial infarction and cancer), delivering small molecule drugs to tumors with high specificity, imparting cell permeability to otherwise impermeable peptides, protecting bioactive peptides from proteolysis in harsh conditions (e.g., stomach acid and whole blood), and transporting proteins into traditionally difficult-to-transfect cell types, including stem cells. Poly(peptide) materials offer new properties to both the constituent peptides and to the polymers, which can be tuned by the design of the oligopeptide sequence, degree of polymerization, peptide arrangement on the polymer backbone, and polymer backbone chemistry. These properties establish this approach as valuable for the development of peptides as medicines and materials in a range of settings.